Evaluasi Usability Sistem Computer-Based Test (CBT) Pada SMA Negeri 1 Bojonegoro - Larasati Budi Sinarahwulan; Mochamad Candra Saputra; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
SMA Negeri 1 Bojonegoro is a school that successfully gets the predicate as a school with national integrity from the Ministry of Education and Culture. Since then, SMA Negeri 1 Bojonegoro has been using Computer-Based Test (CBT) to maintain and enhance the predicate. However, the problems that occured in the implementation of this CBT system are the network not working properly, rotating blackouts, limited computer laboratories, teachers can't asses processes that require long descriptions or counts because CBT is only for multiple choice questions, and CBT system are lack of security. To evaluate this system, PSSUQ questionnaires were distributed, that consists system quality, information quality, interface quality, and overall quality to students of SMA Negeri 1 Bojonegoro as a system users. Then the results of the questionnaire were analyzed using the method of Importance Performance Analysis (IPA). The result of the analysis showed that the CBT system of SMA Negeri 1 Bojonegoro has not comply with the user expectation because the average of gap analysis resulted between importance and performance of -0.83 or <0. From quadrant analysis result, it can be determined recommendation to improvement based on HHS Usability Guidelines. Recommendations to improvement for the CBT system were carried out for items that included in quadrants A, C, and D.